Analisi contrastiva degli errori più spesso commessi da studenti di italiano madrelingua polacca - Dargenio, Matteo (Educazione Linguistica Language Education, 2016)
A correct error analysis can be very valuable not only to improve knowledge of language teaching, but also to examine the grammatical structures of two or more languages from a contrastive perspective. Contrastive analysis can also be very valuable for a teacher who can improve his or her expectancy grammar and in this way prevent a student from the most problematic linguistic structures. This paper will examine, from the contrastive perspective, the Italian grammatical structures, which are very complex for Polish students. The analysis has been performed based on the observation and classification of errors made by Polish students during remedial classes.